Speaking Confidently: How Project-Based Learning Can Improve Student Communication - Ida Ayu Oka Purnami; I Gusti Ngurah Bagus Yoga Widiadnya (Universitas Pendidikan Ganesha, 2024)
Difficulty in speaking English fluently and confidently is one of the skills that language learners find difficult to master. Students from cultures with different communication styles or expectations may find it difficult to adapt to the conventions of conversation in English. Project-based learning has become a popular pedagogical approach in recent years. By providing students with opportunities to apply their knowledge in practice, project-based learning can improve students' motivation, creativity, and critical thinking skills. This study aims to analyze the application of project-based learning in improving students' engagement and learning outcomes in speaking skills. This study used classroom action research, collecting qualitative and quantitative data through speaking tests, as well as qualitative data through observation, pre-test, and post-test. The subjects in this study were thirty-one students from a private high school. The results showed that there was a significant positive effect of project-based learning on students' speaking ability, with an average post-test score of 84.70 and a difference between the average scores of cycle 1 and cycle 2 of 9.52, indicating that there was a significant effect of project-based learning on students' learning outcomes, meaning that there was a positive correlation between the application of project-based learning and the improvement of students' speaking performance. The results of this study strongly support the use of project-based learning as an effective teaching method to improve students' speaking skills.